(untitled) (Indian Journal of Animal Production and Management, 2014)
A study was conducted to find out the socio-personal status of broiler farmers in Lakhimpur and Sonitpur districts of Assam. Fifty numbers of broiler farmers from each district were selected for the study. The data were collected through a well developed and pre-tested interview schedule. The study showed that in both the districts majority of the broiler farmers were Assamese Hindu community, married and having formal education. Averages of 54 per cent farmers were practising broiler farming as a main source of income. Average annual family income was found to be lower in Lakhimpur (Rs. 1.688 lac) than that of Sonitpur (Rs 2.793 lac) district.